(untitled) (Discourse of Law and Administration, 2025)
Dynamic technological development forces the legislator to adapt legal regulations to the new socio-economic environment. It is no different in tax law, which should be updated very often in order to maintain the compatibility of the concepts and institutions regulated in it with economic reality. Thus, the method of regulating fiscal secrecy is one of the challenges for the legislator, who in the era of the changes described above should ensure a compromise between the public interest and the private interest of entities obliged to file tax returns. The aim of this article, in which the author uses not only the dogmatic and historical-descriptive method but also the functional comparative method, will be to indicate the method of regulating exemptions from the obligation to maintain fiscal secrecy in French law. Due to the volume limits of the article, the author will restrict the analysis to two of the eight exclusion groups. The presented analysis of the French legal system, as one of the most technologically advanced, will allow for drawing a number of conclusions in the discussed scope, in particular in relation to the potential application of the analyzed solutions by the Polish legislator. The method of regulating derogations in the scope of fiscal secrecy shown in the work, despite the remarks indicated in the conclusions, it may constitute an impulse for discussion in this aspect, the need for which has already been signaled in Polish doctrine.